Pendidikan Kejuruan: Kajian Teori, Kebijakan, dan Praktik Pembelajaran - Komara, Sasetyo; Iskandar, Ranu (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The dynamics and problems in vocational education can be studied in their entirety through three fundamental aspects, namely the underlying theory, the policies that regulate it, and the learning practices carried out in the field. This study aims to analyze vocational education through three main pillars, namely theoretical studies, policies, and learning practices. This study uses the Narrative Literature Review method. The theoretical study includes an approach from Prosser's Theorem and major learning theories such as behaviorism, cognitivism, constructivism, and humanism, all of which provide a philosophical and methodological basis for designing the vocational learning process. On the policy side, various Indonesian government initiatives are discussed, such as the Link and Match program, SMK Pusat Keunggulan (SMK PK), Merdeka Curriculum, and student competency certification which aim to align education with the needs of the business world and industry. Meanwhile, in the realm of practice, the application of learning models is explained, such as Field Work Practices (PKL), Teaching Factory (TeFa), and practical learning in schools which are designed to strengthen students' work readiness. This aspect emphasizes that the success of vocational education is determined by the synergy between appropriate theory, relevant policies, and contextual learning practices, as well as being responsive to the challenges of the modern world of work.